Ensuring competitiveness in the twenty-first century: features of human resource management - A. A. Madyarov (Вестник университета)
The formation of an innovative economy imposes new obligations on various industries and spheres of activity. The relevance of using new management methods and approaches is increasing. The identification of methods for integrating HR practices used by organizations in the process of digital transformation into the strategic context of the information society is of both scientific and practical interest. The challenges facing the Russian economy motivate the management of Russian organizations to respond in a timely manner to the dynamism of the external environment. The systematization of the main provisions of the Concept of Development of the Russian Federation until 2020, reports of consulting companies, reports of leading Russian banks - the best employers in Russia indicates the readiness of the latter to respond to external threats of the new strategic context. Further improvement of management methods and personnel practices will ensure both the development of the Russian economy as a whole and the attractiveness of Russian organizations for highly qualified specialists. In the context of the information society, it is recommended to continue the consistent and systematic implementation of new management techniques.